Effectiveness of an educational intervention to increase professional nurses' person-centred care competence in long- term care of older people—Quasi-experimental study - Pakkonen Mari; Stolt Minna; Edvardsson David; Charalambous David; Pasanen Miko; Suhonen Riitta. (Scandinavian Journal of Caring Sciences, Wiley, 2025)
Background: Based on previous evidence person-centred care (PCC) as a quality indicator is important in long-term care (LTC) settings for older people. Effective ways to increase nurses' person-centred care competence are missing.
Aim: To evaluate the effectiveness of a continuing education (CE) intervention named 'Person First-Please' (PFP) for improving nurses' PPC competence and its connection to PPC climate.
Methods: Quasi-experimental cluster design with intervention and control groups was carried out in LTC settings for older people. The intervention group (n = 77) received a 10-week CE intervention, with control group (n = 123) working as usual. The primary outcome was professional nurses' PCC competence. Secondary outcome was the PCC climate as perceived by nurses and, residents with their next of kin. Measurements were conducted pre-/post-intervention and after 6 weeks using the validated, Person-centred Care Competence scale and the Person-centred Care Climate questionnaire, staff and patient versions. Data was analysed with descriptive and inferential statistics.
Results: PCC competence was significantly increased in the intervention group and remained after 6 weeks of follow-up. PCC climate increased in the intervention group in total score and also in all sub-scales, across residents with their next of kin. The control group did not show any significant change. Comparisons of PCC competence and PCC climate in time between intervention and control groups confirmed that changes seen between groups were statistically significant in intervention group.
Limitations: Measurements were self-assessments, which may have been affected by bias, especially in context of competence assessment.
Conclusion: The intervention was effective in increasing professional nurses' PCC competence and on person-centred care climate in long-term care settings for older people.